ANALISIS KESANTUNAN BERBAHASA PADA IKLAN SUSU FORMULA - Rohimah, Rani; Apriliani, Rima Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This analysis is motivated by the fact that politeness is very important for the presentation of advertising. The problem statement used in the analysis of this ad is what is the meaning contained in the presentation of SGM and BEBELAC milk advertisements? Does the advertising of SGM and BEBELAC formula produce benefits for children's intellectuals? This research is one of the studies that uses a pragmatic approach because in this study discusses the use of language, and its meaning in an advertisement. Then the objectives to be achieved in the SGM and BEBELAC milk analysis include describing the use of language politeness, which is expected to contain politeness that is beneficial to children's intellectuals, also expected that SGM and BEBELAC formula milk ads contain 5 leech principles that are in accordance with language politeness. Assisted by the leech principle which contains six maxims, the author analyzes the advertisement of two products using instruments of data collection, data analysis, data results. Through a qualitative descriptive research method, the writer finally was able to match the six leech maxims into SGM and BEBELAC milk advertisements. The conclusions of this study include 6 blessed politeness according to leech and the results of discussion on the meaning contained in milk advertising as a good advertisement for children's intellectual benefits.